Farmer Response to Foodgrain Controls in Developing Countries - Chinn, Dennis L. (Quarterly Journal of Economics, 1978)
I. Introduction, 697. — II. To cheat or not to cheat, 698. — III. The inhibited supply curve, 701. — IV. Conclusion, 702.